Linguistic diversity as a challenge and an opportunity for improved legal policy. Issue 1 (2nd January 2021) - Grey, Alexandra; Smith-Khan, Laura
ABSTRACT: This article introduces this Themed Issue, Linguistic Diversity as a Challenge to Legal Policy, and reports a small, peer-reviewed study of the integration of research about language issues in legal contexts in Australian legal education. The article explains that interdisciplinary law and linguistics research has emerged to better understand potential inequalities and injustices. This research speaks to concerns shared across many legal systems because both multilingualism and inter-lingual prejudice are common phenomena across nations. The Themed Issue's eleven contributions draw scholarly attention to specific, current problems in legal contexts which relate to language practices and/or policies about language, arranged around the familiar three branches of the state (legislature, executive, judiciary). The Themed Issue is aimed at endowing readers with motivation and basic knowledge to tread new, language-aware routes towards solutions based on collaborative research and policy reform. In regards to integrating such research into legal education, our NSW and ACT study found few course offerings which focus on an intersection of linguistic and legal scholarship. We therefore suggest the development of electives or the inclusion of such material in core subjects (timely given the 'Priestly 11' compulsory subjects are under review at the time of writing).